PKM INTERNASIONAL INDONESIA-MALAYSIA: Mencapai Keuntungan Dalam Membangun Bisnis Analisis Data - Putri, Dyah Puspitasari Sunaryo; Chasanah, Uswatun; Tryana, Tryana; Alfatiyah, Rini; Dahniar, Tedi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
As technological developments become more advanced, more and more universities are emerging with computer technology-based study programs. One of them is the Computer Science (Software Engineering) Study Program at Universiti Malaysia Terengganu (UMT). In this study program, students gain several skills and one of them is the ability to carry out data analysis, where these skills have great opportunities in work and business. In running a business, participants need to gain knowledge of management and financial management both in theory and practice, so that the data analysis business they run can achieve profits. Pamulang University and UMT have collaborated in the field of Tridharma of Higher Education with number: 041033/MOU/2021/4158. Based on this, Pamulang University and UMT carry out Community Service (PkM) activities. In this activity, participants gain insight into the key to success in running a data analysis business as well as skills in making simple financial report books consisting of: cash book, income statement and balance sheet.